Leadless Pacing: Current Status and Ongoing Developments - Richard G. Trohman (Micromachines)
Although significant strides have been made in cardiac pacing, the field is still evolving. While transvenous permanent pacing is highly effective in the management of bradyarrhythmias, it is not risk free and may result in significant morbidity and, rarely, mortality. Transvenous leads are often the weakest link in a pacing system. They may dislodge, fracture, or suffer breaches in their insulation. This review was undertaken to clarify leadless risks, benefits, and alternatives to transvenous cardiac pacing for bradyarrhythmias and heart failure management. In order to clarify the role(s) of leadless pacing, this narrative review was undertaken by searching MEDLINE to identify peer-reviewed clinical trials, randomized controlled trials, meta-analyses, and review articles, as well as other clinically relevant reports and studies. The search was limited to English-language reports published between 1932 and 2024. Leadless pacing was searched using the terms Micra™, Nanostim™, AVEIR™, single-chamber leadless pacemaker, dual-chamber leadless pacemaker, cardiac resynchronization therapy (CRT), cardiac physiological pacing (CPP) and biventricular pacing (BiV). Google and Google Scholar, as well as bibliographies of identified articles were also reviewed for additional references. The advantages and limitations of leadless pacing as well as options that are under investigation are discussed in detail.